EGO IDENTITY IN THE DRAWINGS OF ADOLESCENTS - Israa Abdulhassain Ali; Kareem Mohsin Ali Sameer Alkabi (American Journals Publishing, 2023)
The research tagged (ego identity in the drawings of adolescents) consisted of four chapters. The first chapter was devoted to the methodological framework of the research. The research problem ended with the following question: What is the identity of the ego in the drawings of adolescents? It also included the aim of the research, its importance and the need for it. As for the second chapter, it dealt with three topics; The first was titled The Concept of Identity, while the second dealt with: adolescence and adolescent identity, and the third dealt with teenage drawings. While the third chapter was devoted to research procedures, the researchers chose a sample of (100) male students in middle school in an intentional manner. The sample was tested twice, the first through the ego identity questionnaire, and the second through drawing. The data of the two tools were analyzed to extract the results. As for the fourth chapter, it was devoted to the results, including: The identity of the ideological ego is distinguished in the drawings of adolescents through horizontal lines, distorted colors, rough textures, and drawing at the bottom of the paper.2- "The identity of the social ego is distinguished in the drawings of adolescents through the slanted lines and the various textures between smoothness and roughness, and the drawing is at the top of the paper."The research ended with recommendations, proposals and a list of sources.
Keywords: Identity, Ego, adolescents, drawing